Medical Students’ Perception on the Ideal Lecturer Attributes in Problem-Based Learning on the Onion Model Theory - M. Ramses Erlangga; Vivi Meidianawaty; Tissa Octavira Permatasari (GHMJ (Global Health Management Journal))
Background: The success of Problem-Based Learning (PBL) is closely related to an effective discussion process. A good PBL will affect the success of the learning process. In addition, an effective teaching process from lecturers to students is very influential in producing a qualified doctor. Korthagen's Onion Model is a theory that emphasizes layered aspects in communication and can provide an in-depth view of the relationship between lecturers and students in the context of learning, such as PBL.